Sorbus prunifolia (Rosaceae), a new species from Yunnan Province, China - Jing, Huijuan; Fan, Qiang; Guo, Wei; Liao, Wenbo (Phytotaxa, 2016)
Sorbus prunifolia W. B. Liao & H. J. Jing (Rosaceae), a new species of Sorbus sect. Micromeles from Yunnan, China, is described and illustrated here. The new species is closely related to S. aronioides Rehder but can be distinguished by the epiphytic habit; smaller leaves (2.5(3)–5 × 1–2 vs. 6–8 × 2.5–5 cm) that are ovate-lanceolate, oblong-elliptic, or elliptic-lanceolate with distinctly rusty-brownish tomentose along veins when young; gradually glabrescent, densely brownish hairy rachis and pedicels when young; sparsely brownish hairy hypanthium and sepals; smaller inflorescence (2–3.5 vs. 3.5–5 cm in diam.); fewer lateral veins (6–8 vs. 7–10 pairs); shorter petioles (3–6 vs. 5–10 mm) and styles (2 vs. 2 or 3, rarely 4); and subglobose pomes with small lenticels (vs. ovoid, usually without lenticels).